The Poetics Of Printing Space And The Title In "Sayyaf Al Zohoor" Text For Muhammad Al Maghoot - Basal , Muhammad; Rostom, Ronia (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The "text" print space includes the method of designing the cover, placing reviews and conclusions, organizing chapters, forming titles ... and others. It opens up an interpretive horizon for literary research, such as this research that tries to show the importance of the written effect of line type, colors, sequential pattern, whiteness, blackness, and page design, in fueling the audience's imagination. The research confirms that the process of choosing the title is the most difficult stage that the author of the text goes through, and he occupied a special place in the arenas of literary creativity, which made the urgent need to develop his own and independent science, which is the "heading science". This research comes as an attempt to read the book “Sayf al-Zuhur” by Muhammad al-Maghout, using all these procedural tools, while trying to adhere to the limits of what is permitted by moral decency and sound knowledge based on what the text says, so it does not force him to what is not in it.